(untitled) (Revista Torreón Universitario, 2022)
When we speak of professional ethics in the daily work of the Public Accountant in order to strengthen the work of companies as a challenge to perform a job with quality, efficiency and effectiveness we mean that the Public Accountant, must act with much belligerence and adherence to the rules and ethical principles of the profession, which leads to having a behavior adjusted to the code of ethics of the profession. In the same way, the Public Accountant, product of his vast experience in the field of accounting and finance, works as an advisor, consultant who develops his professional competence in accounting and finance in order to obtain better results of understanding between the entity and his professional ethics at the service of those who require him to adhere to the rules and procedures established in each entity where he operates. The public accountant in the development of his professional work must comply with the standards established by the International Federation of Accountants (IFAC), which states that in the development of the profession must accept responsibility for the public interest demanded by society in this case the companies, according to their requirements and according to their various activities. The Public Accountant to better develop his work must be trained and acquire constant knowledge that allow him to perform in the field of accounting with better preparation, professional experience and values of training.